Development of science assessment instruments based on entrepreneur - Indah Sukmawati; Sarjono Sarjono (Journal of Science Education Research, 2019)
This study aims to produce (1) an instrument of assessment of learning outcomes for entrepreneurship-based science and (2) a questionnaire of student entrepreneurial interest. This study is a research and development (RnD) with reference to the modified Borg and Gall. The research period was from August 2019 to November 2019 at SMP Negeri 3 Pemalang involving a total of 307 students. The content validation index by experts with V'Aiken for the test instrument for learning outcomes based on entrepreneurship and student questionnaire interest in entrepreneurship are 0.91 and 0.87, respectively. The results show that at the trial stage based on the MNSQ mean INFIT of 1.00 criteria and the standard deviation of 0.00, it is evident that both the tests and questionnaires are both fit with the PCM 1 PL model. Based on the lowest and highest thresholds of INFIT MNSQ, i.e.: 0.77 to 1.30, the instrument of the science-based learning entrepreneurship and questionnaire interest in student entrepreneurship produce 16 and 8 valid items with reliabilities of 0.89 and 0.85, respectively. So it can be concluded that the developed instrument has a high validity and reliability index, so it is ready to be used by science teachers of SMP or MTs for assessment.